Comparison of player perceptions to mechanical measurements of third generation synthetic turf football surfaces - Cole, D.; Fleming, P.; Roberts, J.; James, D.; Benetti, M.; Wistel, K.; Billingham, J.; Forrester, S. (Sports Engineering, 2023)
Mechanical testing of synthetic turf football surfaces is considered essential to ensure player performance and safety. However, it remains unknown how well the mechanical outputs reflect player perceptions of these surfaces. The first objective of this study was to investigate the agreement between the outputs from the Rotational Traction Tester and the Advanced Artificial Athlete with player perceptions across a range of controlled third generation turf football surfaces. The second objective was to identify the modifications to the Rotational Traction Tester and the Advanced Artificial Athlete configurations and output variables that give the strongest agreement with player perceptions. An indoor test area containing ten third generation turf surfaces with controlled hardness and traction properties was constructed. Each surface was tested using the Advanced Artificial Athlete and Rotational Traction Tester in their current configuration and in several modified configurations aimed at better replicating the player-surface interaction. Using a trained panel paired comparisons technique, 18 University footballers (11 males and 7 females) identified differences in the surfaces based on four sensory attributes Movement Speed, Slip, Leg Shock and Give. Results indicated strong agreement (correlation coefficients between 0.7 and 1.0) across several Rotational Traction Tester and Advanced Artificial Athlete testing configurations and output variables with player perceptions. It is recommended that the current Rotational Traction Tester is improved through added instrumentation to allow surface stiffness to be evaluated (the rate of generation of traction resistance). It is further recommended that the Advanced Artificial Athlete adopts a new algorithm to improve the accuracy of the surface`s Vertical Deformation and Energy Restitution, and the number of drops is reduced from three to one.